Crosstalk between alternative polyadenylation and miRNAs in the regulation of protein translational efficiency - Fu, Yonggui; Chen, Liutao; Chen, Chengyong; Ge, Yutong; Kang, Mingjing; Song, Zili; Li, Jingwen; Feng, Yuchao; Huo, Zhanfeng; He, Guopei; Hou, Mengmeng; Chen, Shangwu; et al. (Genome Research, 2018)
3′ UTRs play important roles in the gene regulation network via their influence on mRNA stability, translational efficiency, and subcellular localization. For a given gene, 3′ UTRs of different lengths generated by alternative polyadenylation (APA) may result in functional differences in regulation. The mechanistic details of how length changes of 3′ UTRs alter gene function remain unclear. By combining APA sequencing and polysome profiling, we observed that mRNA isoforms with shorter 3′ UTRs were bound with more polysomes in six cell lines but not in NIH3T3 cells, suggesting that changing 3′ UTRs to shorter isoforms may lead to a higher gene translational efficiency. By interfering with the expression of TNRC6A and analyzing AGO2-PAR-CLIP data, we revealed that the APA effect on translational efficiency was mainly regulated by miRNAs, and this regulation was cell cycle dependent. The discrepancy between NIH3T3 and other cell lines was due to contact inhibition of NIH3T3. Thus, the crosstalk between APA and miRNAs may be needed for the regulation of protein translational efficiency.
10.1101/gr.231506.117